Development of Malaria Diagnostic Kit Using Quantitative Polymerase Chain Reaction (qPCR) Method Based On Cytochrome C Oxidase Subunit I (coxI) Gene in Indonesia - Valerien, Amanda
Malaria is a human disease caused by Plasmodium falciparum, Plasmodium vivax, Plasmodium ovale, Plasmodium malariae, and Plasmodium knowlesi. Usually, malaria patients who is infected by P. falciparum have a more severe and fatal effects if they are not treated directly. Therefore, we need a rapid diagnostic test which is able to detect the number of P. falciparum specifically. Malaria can be diagnosed by microscopic observation, rapid diagnostic test (RDT) using immunoassay, and quantitative polymerase chain reaction (qPCR). The advantages of using qPCR method are more sensitive, quantitative result, and faster than other methods. Cytochrome c oxidase subunit I (coxI) gene is used as a standard for qPCR because it is conspecific among the Plasmodium species and it has a high copy number within a single parasite. Hopefully, this method can be used in Indonesia as an alternative for the costly RDT method which is currently utilized. The purpose of this study is to design a malaria quantitative diagnosis method caused by P. falciparum infection based on coxI gene in Indonesia. Firstly, decide the sequence from P. falciparum mitochondrial coxI gene that differs from the other four species and design a pair of primer to amplify the sequence. Then, make a standard curve for pUC57.coxI recombinant plasmid which is inserted with the P. falciparum mitochondrial coxI gene sequence by serial dilution of pUC57.coxI recombinant plasmid and continued by amplification using qPCR method. After that, quantify the parasite copy number of sample A040, A076, B014, B034, A047, and A077 based on the standard curve equation. This qPCR method is done using Bioline kit which includes SYBR Green I reporter. The standard curve equation is y = -3.3157x + 34.534 and R²= 0,999. This method is able to detect P. falciparum copy number as low as 32,8 copy number/?L. The copy number in sample A040, A076, B014, B034, A047, and A077 based on the calculations are 162,666; 63,06; 12336,8; 21130,45; 20232,24; and 118473 copy number/?L. In conclusion, the qPCR condition and primers in this study is able to quantify P. falciparum based on the mitochondrial coxI gene.